1985
DOI: 10.1080/07391102.1985.10508426
|View full text |Cite
|
Sign up to set email alerts
|

Probing Stability and Dynamics of Proteins by Protease Digestion I: Comparison of Protease Susceptibility and Thermal Stability of Cytochromes c

Abstract: Protease susceptibility of homologous proteins in their native conformations was studied. This work aims to establish a broad and quantitative basis for the utilization of protease digestion to analyze the local stability of native proteins. Using high-performance liquid chromatography (HPLC) the time course of the proteolytic degradation of intact proteins was quantitatively traced. Rapid separation of peptide fragments with HPLC made possible the elucidation of sequential digestion originating from the cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
3
10
0
Order By: Relevance
“…2 for the cytochromes in D 2 O, and the T m values follow the order: bovine (74 7C) 1 horse Similarly, plots of the 1615-cm -1 aggregation band or a-helical amide Ib (1640-1660 cm -1 ) intensities versus temperature (data not shown) yielded the same T m values, confirming that aggregation accompanies loss of secondary structure as reported for other proteins [20]. The order of the T m values observed here for the three cytochromes agrees well with those reported by calorimetry [12] and CD [7], but the values are over 10 7C lower than those obtained in the absence of 0.2 M KCl [12,17], which was added to the samples in the present study because the limited-proteolysis studies were performed in 0.2 M KCl [7,8]. The perturbing effects of KCl and other salts on cytochrome c conformation [31] would explain the 1 10 7C reduction in our T m values, which cannot be ascribed to the high protein concentrations (4 mM) used in the FTIR studies since a T m of 82 7C was previously reported for the FTIR-monitored thermal denaturation of 5 mM horse c in the absence of KCl [17].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…2 for the cytochromes in D 2 O, and the T m values follow the order: bovine (74 7C) 1 horse Similarly, plots of the 1615-cm -1 aggregation band or a-helical amide Ib (1640-1660 cm -1 ) intensities versus temperature (data not shown) yielded the same T m values, confirming that aggregation accompanies loss of secondary structure as reported for other proteins [20]. The order of the T m values observed here for the three cytochromes agrees well with those reported by calorimetry [12] and CD [7], but the values are over 10 7C lower than those obtained in the absence of 0.2 M KCl [12,17], which was added to the samples in the present study because the limited-proteolysis studies were performed in 0.2 M KCl [7,8]. The perturbing effects of KCl and other salts on cytochrome c conformation [31] would explain the 1 10 7C reduction in our T m values, which cannot be ascribed to the high protein concentrations (4 mM) used in the FTIR studies since a T m of 82 7C was previously reported for the FTIR-monitored thermal denaturation of 5 mM horse c in the absence of KCl [17].…”
Section: Resultssupporting
confidence: 80%
“…Bovine cytochrome c is assumed to be essentially identical in structure to horse c since the two proteins share high sequence identity ( 1 97%). Despite remarkably similar main-chain structures [1,6], cytochromes c from different species exhibit different local stabilities as probed by tryptic digestion ( [7,8], A. Filosa, A.M. English, unpublished results) and 695-nm absorption ( [4,5,9], A. Filosa, A.M. English, unpublished results). The latter measures the integrity of the Fe III -S(Met80) bond since disruption or weakening of this bond results in quenching of the 695-nm absorption and opening of the heme crevice [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, PCH only detects one species after protease digestion of TMR-cytochrome c with trypsin. With 19 potential sites for trypsin cleavage (30), this digest should completely destroy the tertiary structure of cytochrome c and reduce the number of fluorescent species to one, consistent with our observation. Additionally, the brightness of this single species is similar to TMRcysteine, consistent with the notion that the fluorophore is no longer quenched.…”
supporting
confidence: 79%
“…For example, cytochromes c from yeast and horse have amino acid sequences that are >60% identical and their tertiary structures are remarkably similar [1,2]. However, protease susceptibility and thermal denaturation studies have shown that the yeast iso-1-cytochrome c (iso-1-cyt c) is much less stable than the horse cytochrome c (h-cyt c) [3,4] To identify the residues responsible for this large difference in protein stability, site-specific mutagenesis, followed by protein expression and purification from Escherichia coli cells, has been used to obtain yeast iso-1-and h-cyt c variants. We engineered residue substitutions within -helices with the goal of assessing the importance of charge distribution for the stabilization of -helix dipole and for the global stability of cyt c. In particular, we chose to introduce mutations into the N-terminal end of two -helices (the -helix encompassing residues 60 to 70 and the C-terminal helix) (Fig.…”
Section: Introductionmentioning
confidence: 99%